Chronic infections of the small intestine. Issue 2 (March 2015) - Bourke, Billy; Hussey, Seamus
<x xml:space="preserve">Abstract</x> Purpose of review Chronic infections of the small intestine cause significant morbidity and mortality globally. This review focuses on the recent advances in the field of our understanding of selected intestinal infections. Recent findings Primary and secondary immunodeficiency increase the susceptibility to many chronic intestinal infections. Endoscopy and intestinal biopsies are central to establishing a diagnosis of these conditions. Tuberculosis (TB) remains a major global health challenge. Emerging therapeutic agents to counteract multidrug-resistant strains have shown clinical efficacy, but concerns regarding mortality remain. PCR-based diagnostic TB tests have the potential to reduce diagnostic delays, but remain to be validated for intestinal infections. Adjunctive diagnostic imaging modalities can differentiate infections from Crohn's disease with increasing accuracy. Whipple's disease remains rare, but there have been substantial advances in our understanding of the causative organism Tropheryma whipplei. Extended treatment with broad-spectrum antibiotics is effective in most cases. The narrow therapeutic window and limited armamentarium for treating invasive filamentous fungal infections contribute to their significant morbidity and high rates of mortality. Summary The speed and accuracy of diagnosing chronic intestinal infections have improved with recent imaging and laboratory methodologies. Significant research opportunities remain for clinicians and scientists to improve the diagnostic accuracy and clinical outcomes of chronic intestinal infections.